Guerrilla Marketing In India Emerging Opportunities And Challenges (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Guerrilla marketing is an unconventional marketing tool which has  developed importance in the modern market. This concept has enabled  the companies to stand out from the crowd by using cost-effective ways.  Additionally, people are on social networks, and the relationships are  becoming more and more integrated into everyday life. Social media  tactics can be targeted, are inexpensive, and very personalized, and  coordinated with offline street team work. As a result, businesses have  increased the rate of targeting consumers who are on social media  networks by using guerrilla marketing. Even in the season of elections,  many political parties are using this concept to reach every section of the  society. This paper discusses how businesses and political parties have  increased the rate of targeting their consumers and voters respectively  with the help of guerilla marketing and allows it to affect their decisions.  Moreover, the paper explores the challenges and opportunities which  businesses and political parties have with guerrilla marketing. The  paper also examines the present trends of guerrilla marketing in India  and describes the reason why companies and political parties are  adopting it and concludes that guerrilla marketing is something that will  continuously grow in both practice and demand.
Keywords: Guerilla Marketing; Social Media Tactics; Cost-Effective